Intercultural Dialogues About Ancestral Territories in the Province of Buenos Aires, Argentina - Mirta Fabiana Millán; María Gabriela Chaparro; Mercedes Mariano (Íconos)
The objective of this article is to make several ancestral territories in the Olavarría party (province of Buenos Aires, Argentina) visible, focusing on their socio-cultural continuity and space-time interaction based on an intercultural dialogue between the authors. For this purpose, we chose three archaeological sites that have been systematically analyzed and studied by researchers, to rethink them as ancient territories, which from the kimun (knowledge) of the Mapuche people, make other logics about space and time possible. This article is the result of a first experience of coproduction of knowledge that sought, through an exchange of indigenous and academic insights, to promote new knowledges about local identities, their continuity and reemergence. In order to accomplish this task, we worked with a qualitative methodology that articulated sci-entific production with oral testimonies and ancestral knowledge of members of contemporary indigenous communities.